Analisis Keragaman Pangan, Aktivitas Fisik dan Persentase Lemak Tubuh dalam Kaitannya dengan Status Gizi Santriwati di Pesantren Ndalem Dongkelan Kota Yogyakarta: The Relationship between Food Diversity, Physical Activity, and Body Fat Percentage and the Nutritional Status of Young Adult Females at the Islamic Boarding School in Ndalem Dongkelan, Yogyakarta City - Aulia Rahmadini Saputri; Emy Huriyati; Fatma Zuhrotun Nisa (Universitas Airlangga, 2025)
Background: Low dietary diversity and physical inactivity among young adult females are contributing factors to the double burden of malnutrition. In Islamic boarding schools, students often face unique lifestyle patterns with limited physical activity and food choices restricted by available menu options. Objectives: This study aimed to analyze the relationships among dietary diversity, physical activity, body fat percentage and nutritional status of young adult females at the Ndalem Dongkelan Islamic Boarding School in Yogyakarta. Methods: This cross-sectional study used total sampling (n=103). Dietary diversity was assessed using the Minimum Dietary Diversity for Women (MDD-W) from three non-consecutive 24-hour dietary recalls. Physical activity was measured using the International Physical Activity Questionnaire Short Form (IPAQ-SF), and body fat percentage was assessed using the Omron HBF-375 BIA device. BMI determined nutritional status. Data analysis included univariate, bivariate (Chi-Square/Fisher’s Exact), and multivariate binary logistic regression. Results: A total of 85.44% of participants had low dietary diversity, 56.31% were moderately active, and 39.81% had high body fat percentage. Bivariate analysis showed p-values of 0.768 for dietary diversity, 0.001 for physical activity, and 0.001 for body fat percentage. The respective odds ratios were 1.42, 10.9, and 11.7. The 95% confidence intervals ranged from 0.41–4.84, 4.06–29.4, and 4.40–31.0. Multivariate analysis revealed that physical activity and body fat percentage significantly contributed to nutritional status. Conclusions: Physical activity and body fat percentage significantly affect the nutritional status among young adult females in boarding school settings.